Duration–severity–area characteristics of drought events in eastern China determined using a three‐dimensional clustering method. (4th November 2020) - Liu, Bingjun; Liang, Manlin; Huang, Zeqin; Tan, Xuezhi
Abstract: Drought is one of the most destructive types of natural disasters, causing great losses of every aspects worldwide. Using a three‐dimensional (longitude, latitude, and time) clustering method based on gridded 3 month standardized precipitation evapotranspiration index data with a resolution of 0.25° collected for East China between 1960 and 2017, we identified and analysed five characteristics of drought events via the Mann–Kendall (MK) test. The results revealed that this method could capture drought events on the basis of their spatiotemporal characteristics. Drought development processes could be visualized via the spatial expansion of drought patches and the transferring path (reconstructed from the centroids of drought patches observed each month). By applying this identification method to the territory of East China, the occurrence of 174 droughts in the last six decades could be determined; furthermore, their objective existence in the spatiotemporal scale was confirmed by comparing the results with historical records and soil moisture data. The increasing moving speed of the centroids and the non‐repetitive rate of the impacted areas suggests that an increasing number of regions have likely been affected over time by large‐scale drought events. The drought patches associated with all of the events identified in the present study tended to move westward in South China and eastward in southwestern China. The remaining four characteristics (i.e., duration, severity, affected area, and intensity), were used to quantify the degree of drought, along with its development, where significant decreasing trends were found among the first three characteristics. In southwestern China, drought events decreased in frequency, but increased spatially, whereas drought events in southeastern China showed an opposite change. Drought events with a small spatial scale occurred more frequently in coastal regions. The majority of drought events mainly occurred in central and North China and moved northward. Abstract : Big difference is found in the change trend of drought between the western and eastern China and drought centroids move westwards at the longest probability distance, suggesting that the unbalanced dry‐wet distribution will be aggravated in China.